The Effect of English Conversation Videos on Students’ Listening Skill - Arrosyi Dayana Sutrisno (Universitas Cokroaminoto Palopo, 2020)
The purpose of this research was to prove that using an English conversation videos is effective in teaching listening skill. This research conducted in SMP Muhammadiyah 1 Wonosobo. The population of this research is eight-grade students, and the sample is 40 students. The method of this research is quantitative method and using pre-experimental design. To collect the data, the writer used a pre-test, and post-test that given to the students. The resulting score of the data indicated that, the total score of students in the pre-test was 2350 with the average were 58.75. The total student's post-test score is 3080 with an average of 77. The results of the pre-test and post-test were calculated using a t-test. The calculation of the data result indicates that the t-count was 2.26 with t-table is 1.69 at the 0.05-significance level. Therefore, this implies that the alternative hypothesis (H1) is accepted, and the null hypothesis (H0) is rejected. The writer concluded that using English conversation videos on studies in teaching English was effective to improve students’ listening skills.